2009
DOI: 10.1002/jmv.21525
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that methylation of hepatitis B virus covalently closed circular DNA in liver tissues of patients with chronic hepatitis B modulates HBV replication

Abstract: Epigenetic factors may modulate chronic Hepatitis B viral infection by affecting virion gene transcription. The aim of this study was to compare the methylation status of the intrahepatic covalently closed circular DNA (cccDNA) CpG island 2 and HBV replication capability. HBV cccDNA was extracted from liver biopsies of 55 HBsAg-positive patients with chronic hepatitis B (32 HBeAg-positive and 23 HBeAg-negative), and was analyzed for methylation status and quantity. The two Hpa II recognition sequences CCpGG in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 20 publications
5
86
1
1
Order By: Relevance
“…15,16 DNA hypermethylation of CpG island 2 can repress transcription and replication of HBV. [2][3][4] We found that the relative abundances of HBc binding to CpG island 2 were negatively correlated with the levels of DNA methylation at CpG island 2. These data indicated that binding of HBc to CpG island 2 inhibited DNA methylation.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…15,16 DNA hypermethylation of CpG island 2 can repress transcription and replication of HBV. [2][3][4] We found that the relative abundances of HBc binding to CpG island 2 were negatively correlated with the levels of DNA methylation at CpG island 2. These data indicated that binding of HBc to CpG island 2 inhibited DNA methylation.…”
Section: Discussionmentioning
confidence: 75%
“…1 Recent advances have highlighted the epigenetic mechanisms underlying the regulation of HBV cccDNA expression. [2][3][4][5][6] Previous studies have found that hypermethylation of CpG island 2 is associated with an impaired replication of intra-hepatic cccDNA in patients with chronic Hepatitis B (CHB). [2][3][4] Furthermore, hypermethylation of CpG islands is observed in individuals with occult HBV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies, from the first in 1983 (Miller and Robinson, 1983) to those of the present day, have revealed DNA methylation in the HBV genome. In addition, DNA methylation of several viral genes is known to be associated with loss of their expression (Vivekanandan et al, 2008(Vivekanandan et al, , 2009Fernandez et al, 2009;Guo et al, 2009). Nevertheless, very few studies have attempted to analyze the viral methylation of specific sequences.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…In CHB patient, viral and host DNA methylation density varies significantly has been identified as a host defence mechanism to suppress viral gene expression and replication. Furthermore, an up regulation of DNA methyltransferases has been reported in CHB livers that facilitates the methylation of cccDNA and viral genomes affecting protein production and viral replication [74,75] . It has been reported that host DNA methylation is the main mechanism to inactivate relevant genes in HCC [76] .…”
Section: Epigenetic Control Of Cccdnamentioning
confidence: 99%